Ketamine-butorphanol-medetomidine versus butorphanol-midazolam-medetomidine immobilisation of serval (Leptailurus serval) - Zeiler, Gareth Edward (University of Pretoria, 2020)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2019.